Learned control over spinal nociception: Transfer and stability of training success in a long-term study. Issue 12 (December 2017) - Bäumler, Maximilian; Feller, Moritz; Krafft, Stefanie; Schiffer, Manuela; Sommer, Jens; Straube, Andreas; Weinges, Fabian; Ruscheweyh, Ruth
Highlights: 4 months after successful nociceptive flexor reflex (RIII reflex) feedback training, the ability for RIII suppression is maintained. Transfer (use of the learned strategies for RIII suppression without feedback) is successful. This is important for application of RIII feedback training in clinical or day-to-day pain. Abstract: Objective: Healthy subjects can learn to use cognitive-emotional strategies to suppress their spinal nociception, quantified by the nociceptive flexor reflex (RIII reflex), when given visual RIII feedback. This likely reflects learned activation of descending pain inhibition. Here, we investigated if training success persists 4 and 8 months after the end of RIII feedback training, and if transfer (RIII suppression without feedback) is possible. Methods: 18 and 8 subjects who had successfully completed feedback training were investigated 4 and 8 months later. Results: At 4 months, RIII suppression during feedback and transfer was similar to that achieved at the final RIII feedback training session (to 50 ± 22%, 53 ± 21% and 52 ± 21% of baseline, all differences n.s.). At 8 months, RIII suppression was somewhat (not significantly) smaller in the feedback run (to 64 ± 17%) compared to the final training session (56 ± 19%). Feedback and transfer runs were similar (to 64 ± 17% vs. 68 ± 24%, n.s.). Concomitant reductions in pain intensity ratings were stable at 4 and 8 months. Conclusions: RIII feedback training success was completely maintained after 4 months, and somewhat attenuated 8 months after training. Transfer was successful. Significance: These results are an important pre-requisite for application of RIII feedback training in the context of clinical pain.